Corporate Policy Strategy Based on Comparison of Financial Performance Due to the Impact of the Covid-19 Pandemic - Wiwik Andriani; Rangga Putra Ananto; Dandi Aprila; Wina Nofrima Fitri (Ilomata International Journal of Tax and Accounting, 2023)
The analysis carried out to see how far a company has carried out by using the rules of financial implementation correctly and adequately is called financial performance. There are 5 (five) ratios used in assessing a company's financial performance, including liquidity ratios, leverage ratios, activity ratios, profitability ratios, and market value ratios. This study aims to determine policy strategies based on the results of comparative tests of the financial performance of companies in the technology and infrastructure sector before and during the 2018-2021 Covid-19 pandemic. This study uses secondary data. The sampling technique used was the purposive sampling method. This study used the normality test and paired difference test. The results of this study indicate that the financial performance of technology companies during the Covid-19 pandemic obtained significant results for all variables. In contrast, for the variables in the infrastructure sector companies, only one variable was significant. Based on the comparative test results, a policy strategy is needed to overcome problems related to financial performance experienced by infrastructure and technology companies listed on the Indonesia Stock Exchange. Through the eight determined policy strategies, it is expected to be able to make the company survive and choose the proper steps in developing its business.